Optimizing IT Infrastructure for Business Continuity - Annam, Srinikhil (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
IT infrastructure is a critical value to ensuring business continuity. It describes the means to maximize IT infrastructure for both resilience, scalability, security, and cost-effectiveness. Based on the current adoption trends in hybrid clouds, edge computing, and automation, the research outlines approaches for improving disaster recovery, fault-tolerant systems, and emerging technologies in AI and IoT. It gives concrete recommendations and also emphasizes performance metrics for sustainable IT infrastructure planning. The study relies on the latest technical information, as well as tables and code snippets to illustrate optimization methods.